Goal Programming Model in Tackling The Optimal Building Material for Production Planning - Hendra Cipta; Rina Widyasari (Malikussaleh University, Aceh, Indonesia, 2023)
The goal achieved in the preparation of production planning is more than one. UD Rezeki Berkah is a small business medium-sized enterprise engaged in the production of building materials. UD Rezeki Berkah aims to meet market demand and must consider the costs used during production to maximize profit. Because of these problems, it will be solved with a goal programming model where this method can solve more than one goal to get a model with optimal goal priority. This research provides an optimal solution, namely achieving the target sales volume and production costs within the Rp limit target. 929,128,971, and profit targets reached Rp. 562,751,890 for a period of one year.